Persepsi Siswa Terhadap Pembelajaran Biologi Berorientasi Lingkungan di SMAN 7 Kerinci - Wulandari, Nitra; M, Novinovrita (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to identify and analyze students’ perceptions of the implementation of environmentally oriented biology learning at SMAN 7 Kerinci. The study used a qualitative approach with a descriptive-exploratory design to deeply explore students’ views, experiences, and responses to learning that integrates environmental issues. The research subjects consisted of 10th-grade students selected through purposive sampling technique based on their active involvement in environmentally related biology learning. Data were collected through semi-structured interviews, observation, and documentation, then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, and conclusion drawing. The results showed that students had positive perceptions of environmentally oriented biology learning, especially in improving understanding of environmental concepts, ecological awareness, and caring attitudes towards environmental sustainability. Students also showed higher interest and motivation in learning when biology material was linked to real environmental problems around them. However, several obstacles were still encountered such as limited learning resources and supporting facilities. Overall, this study concluded that environmentally oriented biology learning has the potential to be a strategic approach in shaping students’ knowledge, attitudes, and pro-environmental behavior and supporting the strengthening of sustainable education in schools.